How to maintain and keep low and stable inflation in Argentina - Lupan, Alexandru; Stroukal, Dominik, 1987-; Nikolovová, Pavla, 1982-; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2016)
This study is titled <How to maintain and keep low and stable inflation in Argentina> and its main purpose is to evaluate possible solutions to the inflation crisis in Argentina. The work will specifically look at the monetary history of Argentina until the most recent days, then it will examine causes of Argentinian inflation and present possible solutions to it. Finally, it examines them and come up with the best theoretical plan.
Vedoucí práce: Dominik Stroukal
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta, 2016
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2016
Způsob přístupu: Internet
Keywords: ekonomická a regionální studia latinské ameriky [obor dipl. práce]; diplomové práce; master's theses